Perseverance in mathematical reasoning of climber students solving linear equations in one variable - Ade Kumalasari; Rohati Rohati; Sri Winarni; Marlina Marlina; Annisa Nur Rasyid (Universitas Hamzanwadi, 2026)
Research on mathematical reasoning has increasingly recognized perseverance as more than